Spatial diffusion and periodic evolving of domain in an SIS epidemic model. (October 2021) - Tong, Yachun; Lin, Zhigui
Abstract: In order to explore the impact of periodically evolving domain on the transmission of disease, we study an SIS reaction–diffusion model with logistic term on a periodically evolving domain. The basic reproduction number R 0 is given by the next generation infection operator, and relies on the evolving rate of the periodically evolving domain, diffusion coefficient of infected individuals d I and size of the space. The monotonicity of R 0 with respect to d I, evolving rate ρ ( t ) and interval length L is derived, and asymptotic property of R 0 if d I or L is small enough or large enough in one-dimensional space is discussed. R 0 as threshold can be used to characterize whether the disease-free equilibrium is stable or not. Our theoretical results and numerical simulations indicate that small evolving rate, small diffusion of infected individuals and small interval length have positive impact on prevention and control of disease.